Blushing Men: A Discovery of Romantic Love in the Middle of Meiji - OGURA, Toshihiko (Japanese Sociological Review, 1999)
This paper aims to examine the encounter of “(romantic) love” and its influence on male youth in the middle of Meiji era, focusing on the figures of “blushing man” in modern literature. According to psychiatry, blush (Erythrophobie) occurs in particular situation, where a self loses suitable way in communicating with indefinite others. Then, we will interpret their blush in literature as disordered representation of shame and fear against the transformation on love relationship, especially images of woman, in new culture. Conventionally speaking, modern styles of love presuppose modern individuals or subjectivity. But, observing these disordered phenomenon, we will disclose that romantic love are primarily experienced as fear against subjectivation, yield by lay women (“shirouto-josei”) who never understand traditional courtship (“iro” or “koi”). And we argue that such a shake of self-identity has truly qualified the discovery of love in modern Japan.